(untitled) (Journal of Global Accounting, 2024)
The study examined the effect of disruptive technology on electronic income of deposit money banks in Nigeria. The population of the study comprised all the twelve listed deposit money banks on Nigerian Exchange Group as at 31st December, 2023. The focus period was 2012 – 2023 which covers twelve years. Ex-post facto research design was adopted and a sample of seven deposit money banks was selected using the purposive sampling technique. Panel data regression technique and E-views 10 Econometric software were employed for the estimations and summary statistics respectively. The tests of hypotheses show that at 1% level of significance, IT Expenditure is positively related with electronic income from a synthesis of the base variables, it can be concluded that a significant relationship exists between technology based innovations’ variables and electronic income of deposit money banks in Nigeria. The adjusted R2 and F-Statistics value are 0.587 and 8.514 respectively, an indication of overall significant relationship between the independent and dependent variables. Based on the results of the study, it is recommended that the monetary authorities should provide appropriate regulations and rules that will help the banks to adapt, adopt or operate financial technology infrastructure in Nigeria.